Dynamic Product Diversity. (26th April 2016) - Caminal, Ramon
Abstract : This paper examines the frequency of new product introductions in monopoly markets where demand is subject to temporary satiation. Consumers' taste for diversity is satisfied over time as new varieties are introduced to the market. If two varieties are introduced in consecutive periods then they become imperfect substitutes and the firm has an incentive to raise prices and sell each one to consumers with higher valuations (better preference matching). Higher frequency can also generate market expansion. However, under strong temporary satiation, better preference matching may dominate and the frequency of new product introductions may become socially excessive.